Macrofinancial Causes of Optimism in Growth Forecasts - Carriere-Swallow, Yan (IMF Working Papers; Working Paper, 2021)
We analyze the causes of the apparent bias towards optimism in growth forecasts underpinning the design of IMF-supported programs, which has been documented in the literature. We find that financial variables observable to forecasters are strong predictors of growth forecast errors. The greater the expansion of the credit-to-GDP gap in the years preceding a program, the greater its over-optimism about growth over the next two years. This result is strongest among forecasts that were most optimistic, where errors are also increasing in the economy's degree of liability dollarization. We find that the inefficient use of financial information applies to growth forecasts more broadly, including the IMF's forecasts in the World Economic Outlook and those produced by professional forecasters compiled by Consensus Economics. We conclude that improved macrofinancial analysis represents a promising avenue for reducing over-optimism in growth forecasts.